Prevalence of Positive Cervical Cancer Screening Tests Past the Age of 65 Years With Prior Adequate Negative Screening. Issue 4 (October 2021) - Sheu, Joanne; Field, Alessia; Viswanathan, Radhika; Minkowitz, Jeremy; Calixte, Rose; Lee, Yi-Chun
Abstract : Objectives: Cervical cancer screening recommendations suggest that cessation can be offered above the age of 65 years if specific prior negative screening criteria are met. We investigated the prevalence of abnormal results in individuals who continue screening despite satisfying the American Society for Colposcopy and Cervical Pathology guidelines for cessation. Materials and Methods: In this retrospective study, medical records 2008–2019 from a single urban hospital-based clinic were queried. Charts were manually reviewed to determine which patients met the American Society for Colposcopy and Cervical Pathology exit criteria but continued screening. Findings detected during the extended surveillance period beyond the age of 65 years were analyzed. Results: Two hundred ninety-six patients met the criteria of additional screening despite meeting guidelines for cessation. Length of the continued additional surveillance period ranged from 1 to 15 years with a mean of 3.98 years and median of 3 years. Thirty-nine individuals had abnormalities during additional surveillance: 25 high-risk human papillomavirus (HR-HPV) positive only with negative cytology, 8 atypical squamous cells of undetermined significance, 3 low-grade squamous intraepithelial lesions, 2 atypical glandular cells of undetermined significance, and 1 high-grade squamous intraepithelial lesion. No cases of cervical cancer were detected. Total rate of abnormalities including HR-HPV positive only was 332.20 per 10, 000 person-years, and cytologic abnormalities alone at 119.25 per 10, 000 person-years. Conclusions: Most findings were HR-HPV positive with negative cytology, which studies suggest may confer low risk of progression in older individuals. In addition, no patient was found to develop cervical malignancy. Despite controversy regarding this recommendation, our data suggest screening cessation may be appropriate with adequate negative screening history.